Predictors of change in bodily pain in early rheumatoid arthritis: an inception cohort study - McWilliams, Daniel F.; Zhang, Weiya; Mansell, Josephine S.; Kiely, Patrick D.W.; Young, Adam; Walsh, David A. (Wiley, 2012)
Objective: To investigate possible predictors for lack of pain improvement after 1 year of treatment for early rheumatoid arthritis (RA).